Body area networks : smart IoT and big data for intelligent health management : 14th EAI International Conference, BODYNETS 2019, Florence, Italy, October 2-3, 2019, Proceedings /: smart IoT and big data for intelligent health management : 14th EAI International Conference, BODYNETS 2019, Florence, Italy, October 2-3, 2019, Proceedings. (2019) - Unknown
No abstract available